Development of temperature-insensitive fibre Bragg grating based pressure transducer - Muhammad Aizzuddin, Abdullah (2019)
Pressure sensors are the essential equipment in the field of pressure measurement. In this study, an aluminium diaphragm-based fibre Bragg grating (FBG) pressure transducer with temperature compensation strategy is presented. FBG-based sensors are good for certain applications, such as biomedical, combustion chamber and pressure vessel; particularly those involving harsh enviroment and high electromagnetic disturbance. One of the greatest challenges for utilising an FBG-sensor based transducer is the unstable output spectrum due to temperature variations. This phenomenon results in a huge variation in pressure readings, thus contributing to accuracy problem. To overcome the problem, this study introduced an approach to solve the inconsistency of sensor output by utilising two FBGs that were bonded at the centre of the diaphragm (FBG sensor) and at the base of the pressure transducer (FBG reference). The inconsistency of wavelength was eliminated by normalising the Bragg wavelength variation from the FBG sensor (∆ƛFBG1) with respect to Bragg wavelength variation from the FBG reference (∆ƛFBG2). The results indicated that the FBG pressure transducer had a sensitivity of 2.8485 nm/MPa at room temperature within the range of 22.9°C to 27.8°C and a linear fitting coefficient of 99.97% in a pressure that ranged from 0 MPa to 0.5 MPa. This FBG pressure transducer with temperature compensation technique was proven to be suitable for the pressure measurement of gas with an average error of 2.32% as compared to the conventional pressure gauge available in market.